A direct evidence of fatigue damage growth inside silicon MEMS structures obtained with EBIC technique - Huy, Vu Le; Kamiya, Shoji (Vietnam Journal of Mechanics, 2014)
Electron beam induced current (EBIC) is a semiconductor analysis technique performed in a scanning electron microscope (SEM) or scanning transmission electron microscope (STEM). It is able to sense defects beneath the surface even invisible by SEM. This paper presents the results of a trial to observe the defect growth inside silicon MEMS structures under fatigue loading by applying EBIC technique. The tests were performed on two specimens fabricated from an n-type single crystal silicon wafer. While the test region of the specimens was repeatedly subjected to compressive stress, EBIC images were obtained to visualize damage evolution which presented by the growth of the dark region on EBIC images. It was proved that the damage is not due to the growth of oxidation layer on the surface of the specimens but due to the growth of intrinsic defects of silicon crystal. The results would be evidences to elucidate that the fatigue damages grow inside silicon MEMS structures but not in oxidation layer.